Atividade antileishmania da fração diclorometano de Libidibia ferrea (Fabales: Fabaceae) - (:unkn) unknown (Universidade Federal do Amazonas - Instituto Nacional de Pesquisas da Amazônia, 2017)
Cutaneous Leishmaniasis is a neglected disease occurring in 98 countries, considered a public health problem. The treatment used for this disease in Brazil has been shown to be ineffective, due to the occurrence of adverse reactions, resistance and because the route of administration is inaccessible to patients residing in furthest regions, besides the long period of application. In recent years, studies have shown that several parts of plants have activity against the protozoan that causes the disease, serving as the basis for the formulation of herbal medicines or as a target for obtaining active principles against leishmaniasis. Libidibia ferrea is a plant species popularly known as jucá, which has been showing great interest in therapeutic research, with several proven biological activities, such as the use of methanolic extract and its fractions evaluated in preliminary studies showed prominent antileishmania activity. Another point of great relevance is in choosing the most effective vehicle to achieve the therapeutic effect. One area that is being well studied is nanostructured, such as the microemulsion, a stable system, considered a great vehicle of different drug classes, where through the transdermal route has shown a good skin permeability, becoming an alternative for local treatment of this disease. Thus, the objective of this work is to evaluate the antileishmanic potential of L. ferrea dichloromethane (DCM) subfractions, evaluating its biological activity in vitro, as well as to develop and characterize a topical microemulsion incorporated with this fraction, performing an in vivo experimental study. The fraction DCM was obtained from the fractionation of the MeOH extract of the fruit of L. ferrea, allowing new fractions by the method of column chromatography. These subfractions were submitted to in vitro assays against promastigotes and amastigotes of Leishmania amazonensis by the Alamar Blue® colorimetric method for cytotoxic activity in peritoneal macrophages, in order to highlight the most effective for antileishmania activity. The DCM fraction was also used for the development of a topical microemulsion. This formulation was characterized by Zeta Potential with droplet size evaluation by dynamic light scattering (DLS), polydispersity index (IPD) and physicochemical analysis. In the in vivo assays, the hamsters (Mesocricetus auratus) experimentally inoculated with L. amazonensis were pooled to receive local treatment with the microemulsion incorporated with the DCM fraction and subsequently euthanized for removal of tissue fragments for apposition print and biopsy culture analysis of injuries. The results of the bioassays showed that subfraction 8 (Sf8) showed activity against L. amazonensis, with IC50 52.33 μg.mL-1. No cytotoxic activity was observed in macrophages exposed to this subfraction. Sf8 reduced the number of amastigotes in vitro by 21.5%. Regarding the in vivo assay the microemulsion controlled the development of the lesion and reduction of the parasitic load, there was no statistical difference comparing with the standard treatment, Glucantime®. This study allowed to identify the subfraction with greater antileishmania activity and the development of a promising formulation for the treatment of tegumentary leishmaniasis, contributing to the elaboration of a proposed phytotherapy, suggesting the continuity of future studies with its association with Glucantime® for purposes to potentiate this therapy.
Keywords: Leishmaniose Tegumentar; Libidibia ferrea; Ensaio in vitro; Microemulsão; Ensaio in vivo; CIÊNCIAS BIOLÓGICAS